Pengaruh Harga Iuran dan Sanksi terhadap Lama Keterlambatan Pembayaran Iuran Program Jaminan Kesehatan Nasional - Ariska, Rinda Minanti; Nuria, Shinta; Budiarto, Wasis (Media Gizi Kesmas, 2024)
Background: Participants of National Health Insurance in Indonesia reached 252,235,864 with 93.05% coverage. East Java is one of the provinces that has not yet achieved Universal Health Coverage or UHC with a membership coverage of 88.6%. For East Java, there are 8 cities/regencies that have reached UHC, with the largest number of inactive participants being in the city of Surabaya with 591,273 or 67.5%. Objectives: The purpose of this study was to determine the effect of contribution fee and penalties on the length of delay in paying contributions to the national health insurance program. Methods: The type of research used was a descriptive study with a cross-sectional design, with a sample of 107 participants in the national health insurance program from noncontribution assistance recipients who had or currently had National Health Insurance contributions in arrears in 2022 in the city of Surabaya. Results: The results showed that the National Health Insurance contribution price variable had a significant effect on the length of delay (α <0.05) with an odds ratio of 0.39 and 95% CI (-1.892 to -0.010). The formation of sanctions also had a significant effect on the delay in paid National Health Insurance contributions (α <0.05) with an odds ratio of 0.32 and a CI of 95% (-2.068 to -0.201). Conclusions: There was a significant influence between the price of National Health Insurance contributions and sanctions on the length of delay in paid National Health Insurance contributions. It expected that National Health Insurance participants from the non-contribution assistance recipient group could access National Health Insurance services to know National Health Insurance regulations and could pay contributions on time so that their membership status remained active.